APPLICATION GRAPHOANALYTICAL METHOD FOR ASSESSING THE CHANGE IN THE SPEED OF MOVEMENT OF VEHICLES MEANS AFTER REPAIR OF HIGHWAYS - Kamenchukov, Alexey (Journal of Applied Engineering Science, 2019)
The article deals with the issues of improving the quality of repair and reconstruction of highways design works. The main criterion of assessing the effectiveness of work is the hypothesis that the speed of vehicles depends directly on the condition of the road pavement and the elimination of defects leads to an increase of the traffic speed. The field research was made to measure the speed of vehicles on road sections before and after repair works. The criteria and factors influencing the change in the road speed are determined. The graphic-analytical method is proposed for estimating the service performance of highways based on the prediction of the change of speed